Reattore innovativo per la produzione di gas idrati: risultati delle prime prove sperimentali - COTANA, Franco; ROSSI, Federico; CASTELLANI, BEATRICE; G. Moncada Lo Giudice (2011)
Gas hydrates are crystalline compounds formed by the hydrogen-bonded water molecules in lattice structure that is stabilized by encapsulating a small guest gas molecule (CH4, C2H6, CO2, H2S, H2). Gas hydrates have a large capacity for the storage of gases and are an attractive method for gas filtration and transportation. However, hydrate formation is usually controlled by the rate of crystallization and thus it can be a slow process. A technology that will rapidly and continuously form hydrate is necessary for scale-up. A novel reactor has been designed, built and installed in the laboratories of Fisica Tecnica – Dept. of Industrial Engineering – university of Perugia to form hydrates by injection of water through spray nozzles from the top of the methane-filled reactor. This method allows to maximize interfacial area between reactants and to minimize mass transfer barriers and thermal effects that negatively affect conversion of reactants into hydrate. In addition to the description of the novel apparatus, results of a first set of experimental applications of the reactor for rapid methane hydrate formation are presented.